Strengthening the Spirit: Adapting Multisystemic Therapy (MST) for Native American Youth and Communities - Torres, Roxanna E. (First Peoples Child & Family Review, 2005)
Multisystemic Therapy [MSR] is an evidence based treatment for youth with severe psychosocial and behavioral problems. Discussed are the personal experiences of a Native American student in social work who is engaged in pursuing information on MST for Native youth and communities. Although there is still promise of its efficacy, there are questions on MST’s effectiveness, replicability, and ease of implementation as a program. There is little quantitative and qualitative information to date to support its generalizability across race - no outcome results for Native participants have been disseminated. With goals of strengthening Native families and communities, discussion includes how MST can be adapted for use and programs concerns that should be considered.